APLIKASI CONVERT TEXT TO VOICE MENGGUNAKAN METODE FINITE STATE AUTOMATA (FSA) - Heru Sutejo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
The purpose of this research conducted at the information section at Sentani airport is to be able to design and build an application system for converting text to voice using the FSA method, so that later this application system can help inform information at Sentani airport. The results of this study are a text to voice conversion application system built to assist in informing Sentani airport, by implementing the FSA method at Delphi, the research obtained a text to voice conversion application with input and output in Indonesian and English, and contains an information report; the method used to break words into syllables in the text-to-speech conversion application program is the FSA method, the results of the broken syllables are then voiced so that the program produces a sound that matches the expected results; as well as in applying the algorithm method to Delphi programming utilizing several operating functions including insert, save, delete, clear, print, and play sound so that the program can run